2012
DOI: 10.5539/ijc.v4n5p62
|View full text |Cite
|
Sign up to set email alerts
|

UV-Irradiation Effect on the Photodegradation of Plasticized Poly (Ortho, Meta, and Para-Fluorostyrene) Isomers in Solid Films

Abstract: The photostability of thin films of poly (Fluorostyrene) isomers was studied by irradiation with UV-light, in presence of air at room temperature. The irradiated polymer films were exposed to different intervals of time and the degradation process was investigated with absorption, fluorescence and FT-IR spectroscopic methods. The influence of phthalate and terephthalate plasticizers on photo-oxidative degradation was also investigated. Blending with these plasticizers was found to decrease the stability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…It was also found that the photo-stability of SPS was reduced by blending with phthalates and terephthalates plasticizers [31]. Phthalate plasticizers were more efficient in the increase in the photodegradation of irradiated polymeric chromophores in solid films [11] [12].…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…It was also found that the photo-stability of SPS was reduced by blending with phthalates and terephthalates plasticizers [31]. Phthalate plasticizers were more efficient in the increase in the photodegradation of irradiated polymeric chromophores in solid films [11] [12].…”
mentioning
confidence: 89%
“…On the other hand, polymeric additives were found to accelerate the radiation-induced degradation of polystyrene and substituted polystyrene films [6]- [12]. It was reported that the photo-stability of PS was reduced by the addition of bromine containing flame retardant, and appeared to depend upon the chemical structure of the polymeric additives [29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from Fig. 6 and Tables 1, 2, and 3, modifications were also noticed in various absorption bands in the FTIR spectra in the region (2,000-1,000 cm 21 ) of blended p-PFS with 0.0%, 1.0%, 3.0%, and 5.0% DBP, upon irradiation for 3.0 h. It showed an increase in the intensity of the absorption band at (1,721 cm 21 ) with an increase of irradiation time [38], and with the increase in amount of added plasticizer. This may increase in the formation of carbonyl compounds that resulted from the photo-oxidation of polymeric chains in the presence of atmospheric oxygen.…”
Section: Ftir Absorption Spectra For Irradiated and Nonirradiated Purmentioning
confidence: 78%
“…In an earlier study, it was reported that the FTIR spectra of irradiated PFS isomers showed an increase in the absorbance in many bands associated with a clear shift of energy at (1,582-1,449 cm 21 ) for o-PFS, at (1,588-1,449 cm 21 ) for m-PFS, and at (1,506 cm 21 ) for p-PFS [38]. The shifts in these ranges were attributed either to C5O stretching vibration of aromatic ketones or to the stretching vibration of the substituted benzene ring [8].…”
Section: Ftir Absorption Spectra For Irradiated and Nonirradiated Purmentioning
confidence: 96%